O Serviço Social no Ministério Público do Estado de São Paulo: gênese e desenvolvimento do trabalho profissional do (a) assistente social - Silva, Cíntia Aparecida da (2017)
This dissertation analyzes genesis and development of professional work by social workers at São Paulo Prosecution Service (MPSP). For this purpose, the object of study aims to evaluate social meaning of Social Work in the institution through two interconnected thematic axes, namely: 1) Analysis of Prosecution Service as a State institution within Brazilian political scenario, describing change movements in its traditional functions since the 1960s, and some implications after Brazil’s Constitution of 1988, which explains the demand for hiring social workers as its staff professionals; 2) Analysis of Social Work at MPSP, considering its genesis and development, focusing on professional work process and their inclusion in institutional work processes. Through these analytical axes, bibliographical and documentary research was carried out in theoretical productions in the field of Social Work, Law, Social Sciences, Political Science, and institutional documents in order to enhance reflections on how Law and Social Work meet social demands and embody them. For data collection, qualitative research was conducted through semi-structured script interviews with 11 subjects (06 were social workers, 04 public prosecutors, and 01 jurist). Taking into account this research on Social Work professionals at MPSP, and on contradictory movements in society, conclusions support MPSP as an important professional area for social workers, as well as remarking the widespread institutional socio occupational positions to be held eventually. For this purpose, Social Work must overcome an endogenous vision and critically consider institutional determinants and social demands in order to build collective work proposals